Drivers of Probation Revocation in Pulaski County, Arkansas - Gu, Mofan (Criminal justice and behavior, 2023)
Probation has received relatively little research attention. In this exploratory two-study inquiry, we first analyzed quantitative data to identify factors driving probation revocation in Pulaski County, Arkansas, among 10,260 individuals (mostly male and African American) between 2015 and 2019 (Study 1). We found individuals with felony histories were significantly more likely to be revoked (aOR 17.2 for one or two convictions; aOR 25.1 for three or more convictions). Other predictors include lower education, younger age at first sentence, unemployment, and substance use. In Study 2, we conducted 20 in-depth qualitative interviews with 12 key stakeholders and 8 individuals with probation experience. We found that client financial instability, substance use and mental health disorders, stakeholder risk avoidance, officer caseload, and lack of accessible resources/services contributed to probation revocation. We conclude with recommendations for changes to probation policy and practice, including officer training, alternatives to incarceration, service expansion, and community engagement.